KEBIJAKAN AFIRMATIF PENGAKUAN DAN PERLINDUNGAN HAK-HAK MASYARAKAT HUKUM ADAT - Sukirno Sukirno (Faculty of Law, Universitas Diponegoro, 2015)
This research aim to know and analyse load policy of affirmative, and principles which must there are in regulation recogniting of customary law community rights. Research method used by normative juridical, and then analysed with legal reasoning. Result of research show UUPA, UU No.1/Pnps/1965 and of UU No.24/2013 not yet seen as policy of affirmative because its recognition still accompanied by condition and discrimination. Therefore regulation come have to load four principle, that is based on empirical research, fourth reference norm of Pancasila, affirmative action, and non discrimination.